Competing for recognition through public good provision - Mattias Polborn (Center for Economic Studies and ifo Institute (CESifo), 2007)
Consider a setting in which several groups of individuals with common interests (clubs) compete with each other for recognition by other individuals. Depending on the context, recognition may be expressed by these other individuals joining a club, or choosing one club to admire. Clubs compete by providing a public good. Some examples for applications of this model include: (i) Churches missionarizing to attract new members; (ii) Open-source software projects and Wikipedia; (iii) professors of an economics department competing to attract graduate students to their respective fields; (iv) artists and researchers aiming for recognition of their work by their peers and the public. Competition between clubs increases the public good provision level, and a sufficiently strong competition effect may even lead to overprovision.
Keywords: H41; 330; Öffentliches Gut; Verein; Soziale Gruppe; Wettbewerb; Theorie